Hybrid molecular/enzymatic catalytic cascade for complete electro-oxidation of glycerol using a promiscuous NAD-dependent formate dehydrogenase from Candida boidinii. Issue 39 (19th April 2017) - Abdellaoui, Sofiene; Seow Chavez, Madelaine; Matanovic, Ivana; Stephens, Andrew R.; Atanassov, Plamen; Minteer, Shelley D.
Abstract : The formate dehydrogenase from Candida boidinii was combined with NH2 -TEMPO to form a novel hybrid anode to oxidize glycerol to carbon dioxide at near-neutral pH. Abstract : Glycerol is a common fuel considered for bioenergy applications. Computational docking studies were performed on formate dehydrogenase from Candida boidinii (cbFDH) that showed that mesoxalate can bind to the buried active site of the holo form predicting that mesoxalate, a byproduct of glycerol oxidation, may act as its substrate. Spectroscopic assays and characterization by HPLC and GC/TCD have shown for the first time that cbFDH can act as a decarboxylase with mesoxalate. From this assessment, cbFDH was combined with NH2 -TEMPO to form a novel hybrid anode to oxidize glycerol to carbon dioxide at near-neutral pH.